An observational study of clinical profile of infants born to pregestational and gestational diabetic mothers - Elango, Sivakumar; Sankarasubramanian, Murugesa Lakshmanan; Marimuthu, Balasubramanian (International Journal of Contemporary Pediatrics, 2018)
Background: Diabetes has now become a global pandemic because of sedentary lifestyle, urbanization, and increasing incidence of obesity and the prevalence is on the rise in developing nations like India. The objective of this study was to study the clinical profile and complications of neonates born to established diabetic mothers and gestational diabetic mothers on insulin. Methods: Over a period of one year, all consecutive live born neonates born to diabetic mothers, both gestational and pregestational (known/established diabetic), on insulin were included in the study. Results: The incidence of hypoglycemia in IPGDM was 2-fold higher (55%) than 25% in IGDM (25%) which was statistically significant (p = 0.009). Congenital anomalies were seen more in IPGDM (41.9%) compared to 18.2% in IGDM which was statistically significant (p=0.02). Conclusions: Congenital anomalies mostly involving cardiovascular, renal system were seen significantly more in newborns born to mothers with established diabetes compared to infants of gestational diabetic mothers. Hypoglycemia was the most common complication followed by hypocalcemia and hyperbilirubinemia.